Methods for controlling rust scale on high-silicon steel
Patent Information
- Application Number
- TW114108299
- Authority / Receiving Office
- TW · TW
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2045-03-05
AI Technical Summary
High-silicon steel products face issues with decarburization and insufficient corrosion resistance due to thin rust scales, requiring additional grinding processes that increase costs and complexity.
A method involving controlled heating, rapid cooling, and slow cooling stages to form a thick rust scale exceeding 7 micrometers on high-silicon steel, using specific air-fuel ratios and cooling rates to maintain low decarburization and enhance corrosion resistance.
The method produces high-silicon steel with improved corrosion resistance and reduced pitting risk, extending the fatigue life of products without additional processing steps or equipment, thus reducing costs and simplifying the manufacturing process.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for manufacturing high-silicon steel, and more particularly to a method for controlling the rust scale of high-silicon steel. [Previous Technology]
[0002] Silicon steel is a ferrosilicon alloy with a silicon content ranging from 0.5% to 6.5% by weight. Due to its excellent magnetic and mechanical properties, silicon steel is commonly used in precision machining, electrical machinery manufacturing, and other fields. High-silicon steels, such as SAE 9254, possess high tensile strength and good fatigue resistance after heat treatment, making them widely used in spring manufacturing and automotive shock absorbers. However, silicon steel is prone to decarburization, but excessive decarburization can adversely affect its mechanical properties. Furthermore, if surface defects (such as rust) exist on the finished silicon steel product, it will significantly reduce the product's mechanical strength and fatigue life. Therefore, high-silicon steel products require strict requirements for surface quality and decarburization levels.
[0003] In the prior art, the Stelmor process is commonly used to cool hot-rolled wire rods. Since the decarburization temperature range for ferrite (also known as α-ferrite) is between 740°C and 830°C, high-silicon steel coils are often cooled to pass through this temperature range as quickly as possible to reduce decarburization. However, because the holding time of high-silicon steel coils at high temperatures is also shortened, the rust scale formed on the surface of the high-silicon steel is relatively thin, resulting in insufficient corrosion resistance. If the storage time is long, localized corrosion can easily form on the surface of the high-silicon steel coils; during subsequent wire drawing, there is also a risk of pitting on the surface of the steel wire. To avoid pitting, an additional grinding process is required to make the surface of the steel wire smooth, so that residual pitting does not cause premature failure of the coiled spring during durability extrusion testing. Therefore, from the perspective of reducing costs and simplifying the process, there is still a need for relevant technical personnel to develop a method for preparing high-silicon steel. [Summary of the Invention]
[0004] In view of the technical defects in the above-mentioned high-silicon steel preparation method, the purpose of this invention is to provide a high-silicon steel preparation method that can simultaneously maintain low decarburization and good corrosion resistance. Moreover, the preparation method does not require an additional grinding process, which can simplify the process and equipment and save energy, thereby reducing the overall processing cost and making it more commercially competitive.
[0005] To achieve the aforementioned objective, this invention provides a method for controlling rust on high-silicon steel, comprising the following steps: Preparation step: placing a high-silicon steel billet in a heating furnace for heating, and then performing a coiling process to obtain a high-silicon steel coil; wherein, the air-fuel ratio of the heating furnace is... The high-silicon steel billet contains silicon (Si), carbon (C), and iron (Fe) with an AFR ratio of 3.5 to 4.0. The process includes a rapid cooling step: the high-silicon steel coil is fed to a first cooling bed zone, where its temperature is reduced to 600°C to 675°C to obtain a pre-cooled high-silicon steel coil; wherein the cooling rate of the first cooling bed zone is 10°C / second to 15°C / second. A slow cooling step is then performed: the pre-cooled high-silicon steel coil is fed to a second cooling bed zone to obtain high-silicon steel; wherein the cooling rate of the second cooling bed zone is 0.4°C / second to 1.0°C / second, and a rust scale forms on the surface of the high-silicon steel, the thickness of which is greater than 7 micrometers (µm).
[0006] This invention mainly achieves this by simultaneously changing multiple parameters of the previous Stelmor cooling bed, controlling the air-fuel ratio of the heating furnace to be within a specific range, and combining a cooling mode of rapid cooling in the first stage and slow cooling in the second stage. Therefore, while maintaining a low amount of decarburization (or even no decarburization) of the ferrous phase in the high-silicon steel, the thickness of the rust scale on the surface of the high-silicon steel can be increased, effectively improving the corrosion resistance of the high-silicon steel, ensuring that the probability of pitting formation is reduced in subsequent applications, and thus giving products made of this high-silicon steel (such as springs) better fatigue life.
[0007] Specifically, based on the total weight of the high-silicon steel billet, the silicon content in the high-silicon steel billet is not less than 1.3 wt%; for example, the silicon content in the high-silicon steel billet may be from 1.3 wt% to 2.0 wt%, but is not limited thereto.
[0008] In some embodiments, the high-silicon steel billet can be medium-carbon steel. Specifically, based on the total weight of the high-silicon steel billet, the carbon content in the high-silicon steel billet can be from 0.5 wt% to 0.6 wt%, but is not limited thereto.
[0009] In some embodiments, the high-silicon steel billet may contain manganese (Mn), chromium (Cr), or combinations thereof, in addition to silicon, carbon, and iron, but is not limited thereto. Specifically, based on the total weight of the high-silicon steel billet, the manganese content in the high-silicon steel billet may be from 0.6 wt% to 0.8 wt%, but is not limited thereto; based on the total weight of the high-silicon steel billet, the chromium content in the high-silicon steel billet may be from 0.6 wt% to 0.8 wt%, but is not limited thereto.
[0010] According to this invention, in the general steel billet heating process, the temperature inside the heating furnace is achieved by burning combustible gases (e.g., coke oven gas, COG) or liquids (heavy oil). Furthermore, the combusted gases form a furnace atmosphere and enter the aforementioned heating furnace to contact the steel billet; therefore, the furnace atmosphere is one of the important factors in the subsequent formation of rust scale on the steel billet. Generally, the main components of the furnace atmosphere include oxygen (O2), water (H2O), carbon monoxide (CO), carbon dioxide (CO2), sulfur dioxide (SO2), etc., and the proportions of these gases are affected by the air-fuel ratio. The air-fuel ratio is defined as follows: Air-fuel ratio = (combustion air supply) / (theoretical air quantity for complete combustion).
[0011] Preferably, in this preparation step, the set temperature of the heating furnace can be between 950°C and 1200°C, but is not limited to this. By using a lower furnace temperature in combination with a lower air-fuel ratio, the method of controlling rust on high-silicon steel of this invention can more easily suppress the decarburization effect of the high-silicon steel billet in the furnace, thus avoiding the situation where the surface carbon content of the high-silicon steel billet is too low.
[0012] Specifically, in this preparation step, the high-silicon steel billet, after heating, can be continuously rolled to form a fully rolled high-silicon steel wire; then, the high-silicon steel wire is conveyed to a continuously rotating coiling machine for the coiling process. Preferably, in this preparation step, the starting coiling temperature of the coiling process can be controlled by adjusting the water volume in the water tank, but it is not limited thereto. In addition, in some embodiments, the high-silicon steel coil includes multiple interconnected coil sections, and each coil section may have the same diameter or different diameters.
[0013] Preferably, in this complete step, the initial winding temperature of the winding process can be between 800°C and 980°C, but is not limited to this. When the initial winding temperature is controlled within the aforementioned range, not only can the growth of rust be promoted, but the total holding time of the high-silicon steel coil in the high-temperature section can also be extended, thus further increasing the thickness of the rust.
[0014] According to this invention, the cooling rates of the first and second zones of the cooling bed can be achieved by adjusting the opening or closing of the insulation cover, the conveyor belt speed, and / or the fan intensity. In some embodiments, the first zone of the cooling bed is cooled by blowing air; for example, the aforementioned blowing method can be continuous strong blowing in the first zone of the cooling bed, and the cooling rate of the first zone of the cooling bed (10°C / sec to 15°C / sec) can be achieved by controlling the air volume. Due to the rapid cooling in the first stage, the high-silicon steel coil can quickly pass through the decarburization sensitive zone of iron ore, which helps to maintain the requirement of low decarburization. In some embodiments, the second zone of the cooling bed can be equipped with an insulation cover and a conveyor belt; the slow cooling step is achieved by closing the insulation cover and controlling the speed of the conveyor belt to achieve the cooling rate of the second zone of the cooling bed (0.4°C / sec to 1.0°C / sec). Specifically, the conveyor belt can be composed of a series of rollers.
[0015] In some embodiments, the first zone of the cooling bed can be divided into two sub-zones, namely the first sub-zone and the second sub-zone; the second zone of the cooling bed can be divided into six sub-zones, namely the third to the eighth sub-zones. The first to the seventh sub-zones can be temperature-controlled through insulation covers, but are not limited thereto; the first to the fifth sub-zones can be equipped with multiple (e.g., two) fans for temperature control, but are not limited thereto. Basically, the insulation covers, the strength of each fan, and the speed of the conveyor belt rollers can all be adjusted as needed to achieve the required temperature, cooling rate, and metallographic structure of the steel. Preferably, the first and second zones of the cooling bed can be a continuously connected conveyor belt system; therefore, the conveyor belts of each sub-zone can be adjusted in a progressive manner, but are not limited thereto.
[0016] In some embodiments, the rust scale may contain ferrous oxide (FeO) and magnetite (Fe3O4), but is not limited thereto. Magnetite (Fe3O4) can be considered a compound of ferrous oxide (FeO) and iron oxide (Fe2O3), and its structure is denser than FeO. Therefore, increasing the proportion (or thickness) of Fe3O4 in the rust scale can further improve corrosion resistance. Preferably, the weight ratio of FeO to Fe3O4 is 2.8:1 to 2:1, but is not limited thereto. According to the iron-oxygen (Fe-O) phase diagram, FeO, Fe3O4, and Fe2O3 are all stable phases above 570°C. Below 570°C, FeO becomes unstable and transforms into Fe3O4 and Fe, with the overall reaction being: 4FeO = Fe3O4 + α-Fe. Therefore, this slow cooling step prolongs the time the initially cooled high-silicon steel coil remains below 570°C, resulting in a higher proportion of Fe3O4 in the rust scale.
[0017] Preferably, the thickness of the rust scale can be greater than 7 µm to 14 µm, but is not limited thereto.
[0018] In some embodiments, the thickness of the rust scale may be 8 µm to 12 µm, and the composition of the rust scale includes FeO and Fe3O4, and the weight ratio of FeO to Fe3O4 is 2.5:1 to 2.1:1, but is not limited thereto.
[0019] In some embodiments, the high-silicon steel can be further collected in a re-forming drum to form a high-silicon steel disc.
[0020] According to this invention, the high-silicon steel and the high-silicon steel coil are suitable for manufacturing springs, especially for springs used in automotive shock absorbers, but are not limited thereto.
[0021] In this specification, the range represented by "small value to large value" means, unless otherwise specified, that the range is greater than or equal to the small value and less than or equal to the large value. For example, an air-fuel ratio of 3.5 to 4.0 means that the numerical range of the air-fuel ratio is "greater than or equal to 3.5 and less than or equal to 4.0".
Implementation Method
[0022] Hereinafter, an embodiment is given to illustrate the implementation of the present invention, and a comparative example is provided for comparison. Those skilled in the art can easily understand the advantages and effects that the present invention can achieve through the content of the following embodiment and comparative example. It should be understood that the embodiments listed in this specification are only used to illustrate the implementation of the present invention and are not intended to limit the scope of the present invention. Those skilled in the art can make various modifications and changes based on their ordinary knowledge without departing from the spirit of the present invention to implement or apply the content of the present invention.
[0023] Example 1: Method for controlling rust scale on high-silicon steel
[0024] Complete supply of high-silicon steel coils
[0025] First, a high-silicon steel billet is prepared, comprising Si, C, Fe, Mn, and Cr; wherein, based on the total weight of the high-silicon steel billet, the C content is 0.50 wt%, the Si content is 1.40 wt%, the Mn content is 0.71 wt%, the Cr content is 0.68 wt%, and the remainder is iron. Second, the high-silicon steel billet is placed in a heating furnace and heated for 70 to 90 minutes; wherein the air-fuel ratio of the heating furnace is 3.8 to 4.0, and the set temperature of the heating furnace is 970°C to 1030°C. Next, after the heated high-silicon steel billet exits the furnace (at a furnace temperature of 1000±30°C), it undergoes a continuous rolling process using a rolling mill to form a fully rolled high-silicon steel wire. Subsequently, the aforementioned high-silicon steel wire is conveyed to a coiling machine for a coiling process to obtain the high-silicon steel coil. A water tank is used to maintain the initial coiling temperature at 890±30°C. Furthermore, the relevant process conditions are summarized in Table 1.
[0026] Rapid Cooling Steps
[0027] The high-silicon steel coil is conveyed to the first zone of the cooling bed, where its temperature is reduced to 610°C to 650°C, resulting in a pre-cooled high-silicon steel coil. The first zone of the cooling bed comprises a first sub-zone and a second sub-zone, both with a cooling rate of 11.5°C / s to 13.8°C / s. Furthermore, each of the first and second sub-zones is equipped with an insulation cover, a conveyor belt consisting of a series of rollers, and a fan to control its cooling rate. The relevant process conditions are summarized in Table 1, and the cooling rate and residence time of each sub-zone are recorded in Table 2-1.
[0028] Slow cooling steps
[0029] In this step, the initially cooled high-silicon steel coil is conveyed to the second cooling bed zone to obtain high-silicon steel material, on which rust is formed; wherein, the initial temperature of the second cooling bed zone is 610°C to 650°C; the second cooling bed zone sequentially includes a third sub-zone, a fourth sub-zone, a fifth sub-zone, a sixth sub-zone, a seventh sub-zone, and an eighth sub-zone, the cooling rate of the third to seventh sub-zones is 0.4°C / second to 0.8°C / second, and the cooling rate of the eighth sub-zone is 0.6°C / second to 1.0°C / second. Furthermore, the third to seventh sub-zones are each equipped with an insulation cover, the third to eighth sub-zones include a conveyor belt composed of a series of rollers, and the third to fifth sub-zones are each equipped with a fan, thereby controlling the cooling rate of each sub-zone. In addition, the relevant process conditions are summarized in Table 1, and the cooling rate and residence time of each sub-zone are recorded in Table 2-1.
[0030] In this embodiment, the high-silicon steel can be further collected in a re-forming bucket to receive the high-silicon steel, thus finally forming a high-silicon steel disk.
[0031] Comparative Example 1
[0032] The manufacturing method of the high silicon steel in Comparative Example 1 is generally the same as the method for controlling the rust of high silicon steel in Example 1 above, and the same high silicon steel billet is used. However, the main difference in the process is that the air-fuel ratio, the initial coiling temperature, the cooling rate of the first zone of the cooling bed, the initial temperature of the second zone of the cooling bed, and the cooling rate of the second zone of the cooling bed used in Comparative Example 1 are not completely the same. Detailed information is shown in Table 1 and Table 2-2.
[0033] Table 1: Process conditions of Example 1 and Comparative Example 1 Process conditions Example 1 Comparative Example 1 Complete steps Bake temperature (°C) 1000±30 1000±30 air-fuel ratio 3.8 to 4.0 Greater than 4.0 to 4.2 Initial winding temperature (°C) 890±30 810±30 rapid cooling steps Cooling rates (°C / s) for sub-regions 1 and 2 11.5 to 13.8 5.0 to 9.0 Slow cooling steps Starting temperature (°C) of the second zone of the cooling bed 610 to 650 ≥570 and <610 Cooling rates (°C / s) for sub-regions 3 to 7 0.4 to 0.8 0.9 to 1.3 Cooling rate of sub-region 8 (°C / sec) 0.6 to 1.0 0.8 to 1.2 Temperature at which the material falls into the reforming barrel (°C) 510 to 550 470 to less than 510 Table 2-1: Cooling rates and residence times for the first sub-region (I) to the eighth sub-region (VIII) of Example 1 I II III IV V VI VII VIII cool down rate (°C / second) 11.5 to 13.8 0.4 to 0.8 0.6 to 1.0 Stay time (Second) 8 to 16 10 to 18 11 to 19 13 to 21 15 to 23 19 to 27 23 to 31 40 to 50 Table 2-2: Cooling rates and residence times for sub-regions 1 to 8 (VIII) of Comparative Example 1 I II III IV V VI VII VIII cool down rate (°C / second) 5.0 to 9.0 0.9 to 1.3 0.8 to 1.2 Stay time (Second) 8 to 16 8 to 16 8 to 16 8 to 16 8 to 16 10 to 18 11 to 19 24 to 32
[0034] Experiment 1: Evaluation of whether the iron structure of fertilizer granules is decarburized
[0035] In this test example, the high silicon steel prepared in Example 1 and Comparative Example 1 were cut into 10 cm lengths as test samples. Each test sample was then cross-cut and embedded, with the surface parallel to the rolling direction and thickness direction as the observation surface.
[0036] An optical microscope (manufacturer: ZEISS, model: Axio Scope A1 MAT) was used to photograph the metallographic structure of the test samples at 100x magnification to observe whether a decarburized layer existed in each test sample. Decarburized layer depth detection software (manufacturer: Digi-Imager; international standard: JIS G 0558) was used to define the depth of the decarburized layer from its initial position to the outer surface of the test sample. The observation results are shown in Table 3. No decarburized layer was observed in either Example 1 or Comparative Example 1; therefore, its thickness was recorded as 0 μm.
[0037] Example 2: Evaluation of rust thickness and composition
[0038] In this test example, the high-silicon steel prepared in Example 1 and Comparative Example 1 was first cut into 10 cm lengths as test samples. Then, each test sample was transversely cut and embedded, with the surface parallel to the rolling direction and thickness direction as the observation surface. Next, it was observed with the optical microscope of Test Example 1 (magnification of 1000x), and the total thickness of the surface rust and the thickness of FeO and Fe3O4 were measured by the scale.
[0039] Due to the rust growth process, FeO mainly grows in the inner layer, while Fe3O4 grows on the outer layer (i.e., the area closer to the outer surface). Therefore, there is a boundary between FeO and Fe3O4, which can be observed and determined by the aforementioned optical microscope. Since FeO and Fe3O4 have similar densities, in this experimental example, their weight ratio was directly calculated from their thicknesses without using other instruments for analysis.
[0040] Test Example 3: Corrosion Resistance
[0041] In this test example, 25 cm long sections of high-silicon steel prepared in Example 1 and Comparative Example 1 were cut as test samples. According to the ASTM D610-12 standard method, the test samples were placed in an environment with a temperature of 50°C and a relative humidity of 95% for 240 hours before being taken out and the corrosion level on the test samples was observed. If the rusted area is greater than 0.3% and less than or equal to 1.0%, it is rated as Grade 6; if the rusted area is greater than 1.0% and less than or equal to 3.0%, it is rated as Grade 5; if the rusted area is greater than 3.0% and less than or equal to 10.0%, it is rated as Grade 4; if the rusted area is greater than 10% and less than or equal to 16.0%, it is rated as Grade 3; if the rusted area is greater than 16.0% and less than or equal to 33.0%, it is rated as Grade 2; if the rusted area is greater than 33.0% and less than or equal to 50.0%, it is rated as Grade 1; if the rusted area is greater than 50.0%, it is rated as Grade 0. The observation results of Example 1 and Comparative Example 1 are listed in Table 3.
[0042] Table 3: Decarburized layer thickness, average rust thickness, weight ratio of FeO to Fe3O4 in the rust of the granulated iron microstructure in Example 1 and Comparative Example 1, and corrosion resistance evaluation results. Example 1 Comparative Example 1 Decarburized layer thickness (µm) 0 0 Average thickness of rust scale (µm) 10 4 The weight ratio of FeO to Fe3O4 7:3 (2.33:1) 3:1 Rating of surface rust level Level 5 Level 1
[0043] As shown in Tables 1 and 3, the method for controlling rust on high-silicon steel in this invention does not require complex processing procedures or the purchase of expensive new equipment systems. It can achieve a thicker rust layer on the high-silicon steel using a simple and efficient method by simultaneously adjusting multiple parameter combinations within the existing preparation system. This improves the corrosion resistance of the high-silicon steel, thereby extending the fatigue life of products made from it. Therefore, the method for controlling rust on high-silicon steel in this invention also has the advantage of energy saving.
[0044] Furthermore, further observation of the high-silicon steels prepared in Example 1 and Comparative Example 1 reveals that the high-silicon steel formed by the method for controlling the rust scale of high-silicon steel of this invention not only obtains a significantly thicker rust scale, but also has a higher proportion of Fe3O4 in the rust scale, thus making it more corrosion resistant.
[0045] In conclusion, the method for controlling the rust scale of high-silicon steel in this invention can indeed produce high-silicon steel with a thicker rust scale in a simple and cost-effective manner, and has considerable potential for commercial implementation.
[0046] Although the foregoing description has explained many features, advantages, and structural details of the invention, the above embodiments are merely examples for the purpose of illustration, and are not intended to limit the scope of the patent application of the invention. All other changes, modifications, and alterations made without departing from the disclosure of the invention should be included within the scope of the patent application of the invention. [Simplified Explanation of the Diagram]
[0047] Figure 1 is a metallographic image of the high-silicon steel obtained in Example 1. Figure 2 is a metallographic image of the high-silicon steel obtained in Comparative Example 1. Figure 3 is a photograph of the corrosion resistance test results of the high-silicon steel obtained in Example 1. Figure 4 is a photograph of the corrosion resistance test results of the high-silicon steel obtained in Comparative Example 1. [Biomaterial Storage]
[0049] None
Claims
1. A method for controlling rust scale on high-silicon steel, comprising the following steps: Preparation steps: A high-silicon steel billet is placed in a heating furnace and heated, then coiled to obtain a high-silicon steel coil; wherein the air-fuel ratio of the heating furnace is 3.5 to 4.0, and the high-silicon steel billet contains silicon, carbon, and iron; Rapid cooling step: The high-silicon steel coil is conveyed to the first cooling bed zone, where its temperature is reduced to 600°C to 675°C, resulting in a pre-cooled high-silicon steel coil; wherein the cooling rate of the first cooling bed zone is 10°C / second to 15°C / second; and slow cooling step: The pre-cooled high-silicon steel coil is conveyed to the second cooling bed zone, resulting in high-silicon steel material; wherein the cooling rate of the second cooling bed zone is 0.4°C / second to 1.0°C / second, and a rust scale forms on the surface of the high-silicon steel material, the thickness of which is greater than 7 micrometers.
2. The method for controlling rust on high-silicon steel as described in claim 1, wherein, In this preparation step, the heating furnace is set to a temperature of 950°C to 1200°C.
3. The method for controlling rust on high-silicon steel as described in claim 1, wherein, In this complete step, the initial winding temperature of the winding process is between 800°C and 980°C.
4. The method for controlling rust on high-silicon steel as described in claim 1, wherein, Based on the total weight of the high-silicon steel billet, the silicon content in the high-silicon steel billet is not less than 1.3% by weight.
5. The method for controlling rust on high-silicon steel as described in any one of claims 1 to 4, wherein, The thickness of the rust is greater than 7 micrometers to 14 micrometers.
6. The method for controlling rust on high-silicon steel as described in any one of claims 1 to 4, wherein, The rust scale is composed of ferrous oxide and magnetite; the weight ratio of ferrous oxide to magnetite is 2.8:1 to 2:
1.
7. The method for controlling rust on high-silicon steel as described in claim 6, wherein, The rust scale is 8 to 12 micrometers thick and consists of ferrous oxide and magnetite in a weight ratio of 2.5:1 to 2.1:
1.
8. The method for controlling rust on high-silicon steel as described in claim 6, wherein, The first zone of the cooling bed is cooled by air blowing.
9. The method for controlling rust on high-silicon steel as described in claim 8, wherein, The second zone of the cooling bed is equipped with an insulation cover and a conveyor belt; the slow cooling step is achieved by closing the insulation cover and controlling the speed of the conveyor belt to achieve the cooling rate.
